جارحیت پسندی کے رحجان کا تدارک: تعلیمات صوفیا کی عصری معنویتThe Significance of Sufi Teachings in Eradication the Inclinations of Antagonism (Al-Qamar, 2020)
This investigation is an attempt to reveal the disadvantages and drawbacks of aggression and its prevailing trends in our society. In this regard, the significance of Sufi teachings in eradication the inclinations of antagonism on the family life of Pakistani society have been labelled. The Sufis are a group of practical Muslims whose slogan is the promotion and dissemination of moral thoughts and values based on Islamic teachings such as forgiveness, patience, peaceful co-existence and harmony etc.  These entities teach these values to their followers and cliques too.  Due to their noble and decent character, non-Muslims also get benefitted from these noble personalities and some people embrace Islam. The society are endowed with practical knowledge and practices as well.  These people not only forgive their opponents despite the demonstration of bad manners and rudeness, but sometimes they also reward them with prizes and honors, for this reason, it helps to end the tendency of aggression in our society and promote tolerance in the society. In this way, non-violence, kindness, tolerance and peace are endorsed to establish an ideal society.  In this article, the same issues have been reviewed according to Islamic Sufism perspective. and the events and stories of the Sufis have been described relating to these noble issues.
Keywords: Sufis; Aggression; Islamic Teachings; Sufism; Peace; Society; forgiveness; antagonism